SEXUALITY IN OLDER AGE: A SYSTEMATIC LITERATURE REVIEW - Barbosa de Sousa Junior, José (Revista Gênero e Interdisciplinaridade, 2023)
Sexuality in old age represents an emerging field of study of growing importance, addressing a fundamental aspect of the quality of life of the elderly. This theme presents a comprehensive interdisciplinarity, as it requires the approach of cultural, social, psychological and physical issues, which leads to the understanding that this is a complex topic of high social relevance. In this sense, this article carries out a bibliographical review seeking to consolidate current knowledge about sexuality at this stage of life, analyzing recent and relevant studies. In this way, a search was carried out for publications on the topic, on the CAPES Periodicals Portal, from 2018 to 2023. Among the publications found, selection criteria were applied through which a result was obtained from eight research studies selected for carrying out of the bibliographic review. As a result of the analysis of this research, it was possible to conclude that there is still a need for more interdisciplinary studies that integrate health, psychology and sociocultural contexts for a broader and more inclusive understanding of sexuality in old age, making it possible to overcome stigmas and stereotypes. which are still perpetuated in contemporary times. Furthermore, the importance of an approach with information and guidance policies for these populations is emphasized, in order to promote respect for the diversity and sexual autonomy of the elderly, providing them with a better quality of life.